From Appreciation toward Transformation: Multicultural Values-in-Practice in an Indonesian ELT Classroom - Lisjaya; Siti Mukminatun (Universitas Sarjanawiyata Tamansiswa, 2026)
As multicultural education becomes increasingly important in English Language Teaching (ELT), understanding how multicultural values are enacted through everyday classroom practice remains an important area of inquiry. This study investigated how multicultural values became enacted as multicultural values-in-practice in an Indonesian senior high school ELT classroom. Employing a qualitative case study design, the research drew on classroom observations, semi-structured teacher interviews, and document analysis. The data were analysed using Directed Qualitative Content Analysis (DQCA), guided by Byram's model of intercultural communicative competence and Banks' dimensions of multicultural education as complementary analytical frameworks. The findings demonstrate that multicultural values were enacted not through explicit multicultural instruction but through the interaction between culturally contextualised language-learning activities and responsive teacher mediation. English text genres provided opportunities for students to encounter diverse cultural perspectives, while the teacher's pedagogical decisions transformed everyday classroom interaction into opportunities to cultivate openness, respect, tolerance, and appreciation of cultural diversity. However, opportunities for sustained critical intercultural dialogue remained limited, indicating that multicultural learning was enacted primarily at the level of appreciation rather than transformative intercultural learning. This study proposes that multicultural values-in-practice should be understood as an evolving pedagogical process through which culturally contextualised learning and responsive teacher mediation gradually create conditions for deeper intercultural learning in ELT classrooms.